Local Electronic Structure Perspectives of Nanoparticle Growth: The Case of MgO - Singh, Jitendra Pal; Chae, Keun Hwa (AMER CHEMICAL SOC, 2019)
Herein, we reported nanoparticle growth from the point of view of the local electronic structure by taking MgO as a prototype material. These nanoparticles were obtained from the sol-gel autocombustion process. The precursor formed in this process was annealed for various temperatures ranging from 300 to 1200 degrees C for 0.5 and 1 h. It was observed that the amorphous phase occurred in the material synthesized at an annealing temperature of 300 degrees C for 1 h. This phase transformed to crystalline when the annealing temperature was increased to 350 degrees C. Crystallite size increased with annealing temperature; however, annealing time did not influence the crystallite size. To get deeper insights of modifications occurring at the atomic scale during crystallization growth, the local electronic structure of synthesized materials was investigated by measuring near-edge X-ray absorption fine structure at Mg, O, N, and C Kedges. These results envisaged that Mg2+ ion coordination improved with the increase of annealing temperature. It was also observed that both annealing time and annealing temperature are sensitive to the local electronic structural changes.
Keywords: GRAIN-GROWTH; ZINC FERRITE; IN-SITU; COMBUSTION SYNTHESIS; OXIDE NANOPARTICLES; KINETICS; EVOLUTION; RAMAN; SIZE; XRD